PROJECT-BASED LEARNING ON FOLKLORE TEXTS OF LAMONGAN CITY LEGENDS - nisarizzulma, dhyta romadhona (EDU-KATA, 2024)
This study aims to explore the history of Lamongan Regency through the implementation of the Project Based Learning (PBL) model to teach the skill of writing folklore. The research method used is descriptive qualitative with data sources consisting of transcripts of the folklore about the History of Lamongan Regency. The results indicate that folklore, such as the story of Mbah Lamong who became the first regent of Lamongan, is rich in messages and benefits, such as the importance of wise leadership, the dissemination of religion with virtuous values, as well as courage and dedication. The application of PBL in this learning process enhances students' understanding of local history, inspires them through historical figures, and teaches life values. PBL also makes learning more effective, interactive, and enjoyable, encouraging students to be active, creative, and independent in exploring knowledge. Overall, this study demonstrates that the use of the PBL model has a significant impact on increasing students' interest and understanding of folklore and local history.